Continuous flow photooxidation of alkyl benzenes using fine bubbles for mass transfer enhancement. (2nd February 2022) - Morrison, Gary; Bannon, Ruairí; Wharry, Scott; Moody, Thomas S.; Mase, Nobuyuki; Hattori, Masayuki; Manyar, Haresh; Smyth, Megan
Graphical abstract: Abstract: Selective photooxidation of alkyl benzenes was studied in a custom-built continuous flow photochemical reactor equipped with fine bubble generator and a low power UV light source. Fine bubbles of air were used as an oxidizing agent along with water-soluble sodium anthraquinone sulfonate as catalyst. The fine bubble containing slug-flow system using air was 1.4 times more efficient at lower feed-flow rate of 2 mL/min and 1.8 times more efficient at higher feed-flow rate of 5 mL/min. Ethylbenzene was selectively oxidized in continuous flow to acetophenone at room-temperature, with 90% ethylbenzene conversion and 92% selectivity to acetophenone, with a short residence time of 5 min. The enhanced gas/liquid mass transfer afforded by the fine bubble generator significantly increased reactor productivity, giving rise to high conversion and yield. Due to enhanced mass transfer and greater efficiency, compressed air can be used as oxidant instead of pure O2, thus alleviating potential safety concerns and making the process safer and more amenable for scale up.